2009
DOI: 10.1111/j.1540-6210.2009.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Public Utility Commission Web Sites: Targeting Audiences, Missing Opportunities

Abstract: Research demonstrates that some government agencies are more accomplished than others when it comes to e-government. More generally, various scholars suggest that e-government is moving forward at a relatively slow pace, especially in relation to the sophistication of government Web sites. With these issues in mind, this research utilized interviews with state public utility commission staff members to explore their agencies' experiences with staffi ng, funding, coordinating, and prioritizing their e-governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A study by Moon (2002) on e‐government development in municipalities suggested that a lack of capacity is a major shared barrier to municipal e‐government progress. Three types of capacity—financial, technical, and personnel—play important roles in this regard (Moon 2002; Wood, Bernt, and Ting 2009).…”
Section: Determinants Of Transparency Of Governmentmentioning
confidence: 99%
“…A study by Moon (2002) on e‐government development in municipalities suggested that a lack of capacity is a major shared barrier to municipal e‐government progress. Three types of capacity—financial, technical, and personnel—play important roles in this regard (Moon 2002; Wood, Bernt, and Ting 2009).…”
Section: Determinants Of Transparency Of Governmentmentioning
confidence: 99%
“…Organizational inertia in public organizations is often symbolized by complex administrative rules and red tape and has its roots in law. Wood, Bernt, and Ting (2009) pointed out many barriers to e-government innovation at the managerial level, summarizing employee resistance to using information technology (Ho & Ni, 2004), maintenance burdens (Eschenfelder, 2004), and failure to fully evaluate the efforts of the staff to implement the change (Chen & Knepper, 2005;Specht & Hoff, 2005). Facing resistance, it is not easy to tune up the political voice enough to be heard by government agencies.…”
Section: Motivation To Choose Exploration or Exploitation In Public Omentioning
confidence: 98%
“…A plausible counterargument is that cities with strong mayors face additional political pressure to make more data available (Pardo, Cresswell, and Thompson ). But political pressure is an uneven tool for promoting innovation implementation, with mixed empirical results (Choi and Chandler ; Wood, Bernt, and Ting ). The stability and professionalization associated with council‐manager governments increase the chance for genuine innovation implementation (Rivera, Streib, and Willoughby ; Streib and Willoughby ).Hypothesis Cities with council‐manager forms of government will make more data available across departments than strong mayor cities.…”
Section: Public Sector Innovation and Open Datamentioning
confidence: 99%
“…Some may see open data platforms as an opportunity to improve constituent relations or reduce the costs of using data to produce new services or administrative procedures. Others may view open data platforms as a threat to their security, legitimacy, or operations (Wang and Feeney ; Wood, Bernt, and Ting ).…”
Section: Public Sector Innovation and Open Datamentioning
confidence: 99%